Digital Game-Based Learning and Student Engagement in Elementary Science: Evidence from a Quasi-Experimental Study Using Wordwall - Muhammad Amran; Nur Ilmi; Israyanti Ahmad (ILIN Institute Makassar, 2026)
This study investigates the effectiveness of Game-Based Learning (GBL) in enhancing student engagement in elementary integrated science learning, addressing the issue of limited active participation commonly observed in classrooms. Using a quantitative approach, the study employed a quasi-experimental design with a posttest-only control group. The sample consisted of two fourth-grade classes at UPTD SD Negeri 28 Pare-pare. Class IV.2 served as the experimental group and Class IV.1 as the control group. The experimental group received instruction using a Game-Based Learning approach supported by the Wordwall digital platform, whereas the control group was taught using conventional instructional methods. Data on student engagement were collected through observation and analyzed using an independent samples t-test. The results revealed a statistically significant difference in student engagement between the two groups (p < 0.05). This indicates that students who were taught using the Game-Based Learning approach demonstrated higher levels of engagement compared to those who received conventional instruction. These findings suggest that integrating digital Game-Based Learning tools such as Wordwall can effectively promote active participation and enhance student engagement in elementary science learning